표면 요철이 발달된 캐필러리 적용에 따른 Cu 와이어의 본딩 특성 - 이종현; Jong Hyun Lee; 김주형; Ju Hyung Kim; 강홍전; Hong Jeon Kang; 김학범; Hak Bum Kim; 문정탁; Jung Tak Moon; 류도형; Doh Hyung Riu (대한금속·재료학회지, 50(12), 2012)
In spite of some problems in processability and bondability, Au wires in the microelectronics industry are gradually being replaced by copper wires to reduce the cost of raw material. In this article, the effects of surface roughness enhanced capillaries on thermosonic Cu wire bonding were evaluated. The roughness-enhanced zirconia toughened alumina (ZTA) capillaries were fabricated via a thermal grooving technique. As a result, the shear bond strength of first bonds (ball bonds) bonded using the roughness-enhanced capillary was enhanced by 15% as compared with that of normal bonds due to more effective plastic deformation and flow of a Cu ball. In the pull-out test of second bonds (stitch bonds), processed at two limit conditions on combinations of process parameters, the bond strength of bonds formed using the roughness-enhanced capillary also resulted in values higher by 55.5% than that of normal bonds because of the increase in the bonding area, indicating the expansion of a processing window for Cu wire bonding. These results suggest that the adoption of roughness-enhanced capillaries is a promising approach for enhancing processability and bondability in Cu wire bonding.